The starship children's hospital tonsillectomy: A further 10 years of experience. (27th April 2016) - Mahadevan, Murali; van der Meer, Graeme; Gruber, Maayan; Reed, Peter; Jackson, Conor; Brown, Colin; Mills, Nikki; Salkeld, Lesley J.; Neeff, Michel; Evans, Jan; Anderson, Brian; Barber, Colin
Abstract : Objectives/Hypothesis: Tonsillectomy as a day‐stay procedure remains controversial, although it is an established procedure in New Zealand. We reviewed our last 10 years' experience. Methods: A prospective audit was used to determine unplanned conversion from day‐stay to overnight hospital admission rates and the incidence of postoperative complications. Results: There were 5, 400 tonsillectomies performed over the 10‐year study period (January 2004–January 2015); 71% as outpatients. The unplanned conversion rate to overnight stay was 0.4%. The median age of day‐stay patients was 6.5 years (range 13 months–15 years) compared with those admitted for overnight stay (5 years; range 8 months–15 years). The primary postoperative bleed rate was 0.5% (confidence interval [CI] 0.3%–0.7%), and the combined primary and secondary posttonsillectomy bleed rate was 4.3% (CI 3.8%–5.0%). The rate of patients returning with postoperative complications within 1 month of surgery was 6.3% (CI 5.6%–7.0%). Conclusion: Day‐stay tonsillectomy in the pediatric population is safe when performed using the described guidelines in a facility with appropriate resources. Level of Evidence: 4. Laryngoscope, 126:E416–E420, 2016